Perancangan Data Warehouse Umat Lingkungan Gereja XYZ Menggunakan Metode Star Schema - Andreas Alessandro; Deo Anggoro; Andri Wijaya (Journal Of Informatics And Busisnes, 2023)
The implementation of data warehouse technology at the Catholic Church XYZ, covering multiple regions, has become a common necessity. The use of a data warehouse aims to manage parishioner data more efficiently through a structured data warehouse system. The organized data integration process is the main focus, enabling church administrators to process data quickly and accurately in accessing the required information. By emphasizing the modeling process, the use of the Star Schema as a dimensional model provides ease in understanding data structures, serving as a key source of information for decision-making, especially regarding territorial allocations. This data warehouse design serves as a comprehensive solution for managing integrated parishioner data, supporting various information needs and decision-making processes. In addition to streamlining processes, the implementation of the data warehouse enhances the church's capabilities in addressing the increasingly complex dynamics of the environment.